Spectrofluorimetric Method for Trace Determination of Ce(III) in Presence of Surfactant Triton-X-100 - Tavallali, Hossein; Nejabat, Rozita (Asian Journal of Chemistry, 2010)
A simple, efficient and feasible spectrofluorimetric method has been developed for trace determination of cerium(III). The use of surfactant Triton-X-100 (TX100) was investigated. The fluorescence intensity of Ce3+ was enhanced when 1.16 × 10-6 % (v/v) of TX100 was added and it was measured by a 1 cm quartz cell with luminescence spectrometer at room temperature. The apparent wavelengths were lex = 303.5 nm and lem = 354 nm. The enhanced fluorescence intensity of the system (ΔF) showed 2 linear relationships with the concentration of Ce3+ in the ranges of 50-800 ng/mL and 5-30 μg/mL and correlation coefficient 0.9997 and 0.9996, respectively. The detection limit (S/N = 3) of Ce3+ was 18.70 ng/mL. The influence parameters such as surfactant concentration, pH, temperature and ionic strength were optimized. The quenching effects of some inorganic anions and cations were studied and showed there isn't serious. The presented method was used to determine Ce3+ in synthetic samples, which give satisfactory results.